Development of near-field emission limit from radiated-emission limit based on statistical approach - See, Kye Yak (2013)
This paper discusses a novel approach to transforming a radiated-emission limit (e.g., CISPR 22 and FCC) from the far-field to the near-field region. The proposed approach combines data from a near-field scanner and a gigahertz transverse electromagnetic cell with statistics to establish a simple relationship between a near-field magnetic field and a far-field electric field. It is shown that the proposed approach has the potential to be a simple, quick, and fairly inexpensive tool for electromagnetic compatibility pre-compliance purposes.